(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Cardiac remodeling is important issue after surgical closure of ventricular septal defect. Objective: The purpose of the present study was to evaluate cardiac remodeling by echocardiography by measuring the ejection fraction, fractional shortening, left ventricular internal diameter during diastole (LVIDd) and left ventricular internal diameter during systole (LVIDs) after surgical closure of ventricular septal defect in different age group. Methodology: This prospective cohort studies was conducted in the Department of Cardiac Surgery at National Institute of Cardiovascular Disease (NICVD), Dhaka. Patient with surgical closure of VSD were enrolled into this study purposively and were divided into 3 groups according to the age. In group A (n=10), patients were within the age group of 2.0 to 6.0 years; age of group B (n=8) patients were 6.1-18.0 years and the group C (n=6) aged range was 18.1-42.0 years. Echocardiographic variables such as ejection fraction, fractional shortening, LVIDd, LVIDs were taken preoperatively and at 1st and 3rd month of postoperative values. Result: A total number of 24 patients was recruited for this study. The mean ages of all groups were 12.60±12.09. After 1 month ejection fraction were decreased by 5.97%, 6.71% and 5.66% in group A, group B and group C respectively. After 3 months ejection fraction were increased by 6.13%, 5.13% and 5.14% in group A, group B and group C respectively. After 1 month fractional shortening were decreased by 13.55%, 9.30% and 9.09% in group A, group B and group C respectively. After 3 months fractional shortening were increased by 7.23%, 7.35% and 4.55% in group A, group B and group C respectively. After 1 month LVIDd were increased by 1.97%, 1.91% and 1.32% in group A, group B and group C respectively. After 3 months LVIDd were decreased by 10.84%, 9.89% and 7.34% in group A, group B and group C respectively. After 1 month LVIDs were increased by 2.19%, 2.86% and 1.98% in group A, group B and group C respectively. After 3 months LVIDs were decreased by 11.68%, 10.97% and 8.87% in group A, group B and group C respectively. Conclusion: Cardiac remodeling occurred after surgical closure of ventricular septal defect and remodeling were more significant in younger age group. Journal of National Institute of Neurosciences Bangladesh, 2016;2(2):69-74